IMPROVED HEAT SUPPLY CONTROL SYSTEM - Савка, Надія; Погорілець, Анна (SWorldJournal, 2024)
The principle operation of the coolant supply system to consumers is analyzed. The main problems of heat supply are indicated and ways to solve them are proposed. The main thing in the modernization of heat supply systems is the process automation of con